Microbial signatures in metastatic cancer - Bautista, Jhommara; Fuentes-Yépez, María Paula; Adatty-Molina, Joseth; López-Cortés, Andrés (Frontiers in Medicine, 2025)
Metastasis remains the leading cause of cancer-related death, yet the biological determinants that enable tumor cells to disseminate and colonize distant organs are incompletely understood. Emerging evidence identifies the microbiome, not merely as a bystander, but as an active architect of the metastatic cascade. Microbial communities residing in the gut, mucosal barriers, and within tumors shape metastatic progression by modulating immune surveillance, stromal remodeling, oncogenic signaling, and therapy response. Intratumoral and even intracellular microbes regulate epithelial–mesenchymal transition, angiogenesis, and immune escape, while gut-derived metabolites condition pre-metastatic niches and alter systemic immunity. Technological advances in spatial transcriptomics, single-cell multi-omics, and metagenomics have revealed a spatially organized, functionally integrated microbial ecosystem within tumors, challenging long-held assumptions of sterility in cancer biology. This review synthesizes five converging dimensions of this paradigm: microbial interactions in the metastatic tumor microenvironment; microbiome-mediated immunoediting and metastatic escape; the role of intratumoral and intracellular bacteria in dissemination; spatial-multi-omic approaches to map microbial niches; and microbial biomarkers predictive of metastasis and therapy outcomes. Collectively, these findings recast the microbiome as a critical and targetable determinant of metastasis. Deciphering the tumor–microbe–host triad holds transformative potential for biomarker development, therapeutic innovation, and precision oncology.